2015
DOI: 10.1016/j.ssresearch.2014.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Universalism under siege? Exploring the association between targeting, child benefits and child poverty across 26 countries

Abstract: The long-standing wisdom that universally designed benefits outperform targeted benefits in terms of poverty reduction has come under siege. Recent empirical studies tend to find that targeting is not necessarily associated anymore with lower levels of poverty reduction. In this study, we investigate for a broad set of European countries (1) the relationship between child benefits and child poverty reduction; (2) whether a universal or targeted approach is more effective in reducing child poverty; and (3) the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
61
0
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 31 publications
5
61
0
4
Order By: Relevance
“…This approach is also suggested in recent work by Van Lancker and Van Mechelen (2015) and Van Mechelen and Bradshaw (2013). The findings of this chapter offer additional support for such an approach.…”
Section: Conclusion and Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…This approach is also suggested in recent work by Van Lancker and Van Mechelen (2015) and Van Mechelen and Bradshaw (2013). The findings of this chapter offer additional support for such an approach.…”
Section: Conclusion and Discussionsupporting
confidence: 71%
“…Van Lancker and Van Mechelen (2015) explored the association between targeting of child benefits and child poverty, and found that targeting low-income families resulted in higher levels of poverty reduction. The authors conclude that targeting has a better effect under certain circumstances: when targeting is directed towards lowincome families and when the benefits are generous.…”
Section: Universalism Versus Targeting: An Ongoing Debatementioning
confidence: 99%
See 1 more Smart Citation
“…However in the UK (tax) benefits for families with children are relatively high and targeted towards lower incomes (Van Lancker and Van Mechelen 2014). Anglo-Saxon countries -especially the UK -display higher inequality in earnings and higher poverty (Korpi 2000).…”
Section: Anglo-saxon Countries: Australia and The Ukmentioning
confidence: 99%
“…1 A large body of research has demonstrated that child benefits are of paramount importance in reducing child poverty (Van Lancker and Van Mechelen 2015;Salanauskaite and Verbist 2013;Bradshaw 2012;Kamerman et al 2003;Immervoll et al 2001). This means that child benefit systems have an important redistributive impact, commonly referred to as a vertical equity objective.…”
Section: Introductionmentioning
confidence: 99%